2022
DOI: 10.1002/jhbp.1275
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Tokyo guidelines 2018 for safety and mortality benefit from urgent ERCP in acute cholangitis across different age groups

Abstract: Background The 2018 Tokyo Guidelines (TG18) recommend urgent endoscopic biliary drainage based on acute cholangitis (AC) severity. Therefore, we evaluated the safety and mortality benefits of urgent endoscopic retrograde cholangiopancreatography (ERCP) in different age groups. Methods Using International Classification of Diseases‐10 (ICD‐10) codes, we sampled adult AC patients from National Inpatient Sample. TG18 definition of cholangitis severity was used to identify patients with severe and nonsevere (mild … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Acute cholangitis (AC) is a life-threatening condition that requires early diagnosis and treatment to prevent systemic complications and reduce mortality [ 1 , 47 ]. The Tokyo Guidelines, established by a panel of international experts, have improved diagnostic yield and facilitated decision-making in the early stages of the disease by recommending a combination of clinical, laboratory, and imaging findings [ 6 , 29 , 30 ]. However, there are still cases of AC that are difficult to diagnose and manage [ 13 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acute cholangitis (AC) is a life-threatening condition that requires early diagnosis and treatment to prevent systemic complications and reduce mortality [ 1 , 47 ]. The Tokyo Guidelines, established by a panel of international experts, have improved diagnostic yield and facilitated decision-making in the early stages of the disease by recommending a combination of clinical, laboratory, and imaging findings [ 6 , 29 , 30 ]. However, there are still cases of AC that are difficult to diagnose and manage [ 13 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…AC was diagnosed according to the diagnostic criteria of the 2018 Tokyo Guidelines. The Tokyo Guidelines provide criteria for diagnosing acute cholangitis based on clinical features, laboratory data, and imaging findings [ 6 , 29 , 30 ]. They also provide a severity grading system that classifies acute cholangitis into mild (grade 1), moderate (grade 2), and severe (grade 3) categories based on the presence or absence of organ dysfunction, cholangitis-related symptoms, and inflammatory response [ 6 , 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complications related to cirrhosis, including portal gastropathy, esophageal varices, liver dysfunction, and coagulation impairment, further increase the risk of bleeding in these patients. 14 , 32 Previously performed studies documented different rates of post-ERCP bleeding. Navaneethan et al 7 analyzed the USA Nationwide inpatient sample database and reported that 2.1% of cirrhotic patients developed bleeding after ERCP.…”
Section: Discussionmentioning
confidence: 99%
“…Five years later, she developed BEA stricture, and new intrahepatic calculi were formed, leading to recurrent pyogenic cholangitis and liver abscesses. Furthermore, the patient was subjected to five ERCPs and, finally, one percutaneous transhepatic drainage of the biliary tract in one episode of cholangitis Tokyo II [ 9 ]. The case was discussed in a multidisciplinary conference, and the patient was submitted to a surgical and endoscopic combined approach.…”
Section: Case Presentationmentioning
confidence: 99%